Light Spectrum Variably Affects the Acclimatization of Grafted Watermelon Seedlings While Maintaining Fruit Quality - Filippos Bantis; Christodoulos Dangitsis; Anastasios S. Siomos; Athanasios Koukounaras (Horticulturae, 2021)
In many countries of Europe and Eastern Asia, watermelon production is mainly based on the use of grafted seedlings. Upon grafting, seedlings undergo a period of healing where artificial lighting is provided by light-emitting diodes in controlled chambers in order to accelerate and improve the healing process. The objective of our study was to test the effect of light quality on the final product (i.e., seedlings ready for transplanting) in the nursery, as well as to evaluate the possible implications on fruit quality after field cultivation. Narrow-band blue (B) and red (R) wavelengths, 64–36% R-B (36B), 76–24% R-B (24B), 88–12% R-B (12B), and 83–12% R-B plus 5% far-red (12B+FR) wavelengths were tested. 12B+FR enhanced the root dry weight, root architecture, and maximum photosynthetic rate, while RB combinations generally showed better root system development with increased blue portion. R light induced inferior root dry weight and quality indices (root/shoot and shoot–dry–weight/length ratios), lower gas exchange parameters, and chlorophyll content, but high shoot length and leaf area. B light led to inferior root architecture, lower stem diameter, leaf area, and maximum photosynthetic rate. Both R and B wavelengths showed decreased concentration of macronutrients and trace elements. After field cultivation, fruit quality (i.e., morphology and color), and valuable nutritive characteristics (i.e., phenolics, carotenoids, lycopene, antioxidants) maintained high quality irrespective of light treatments. Overall, 12B+FR performed well in almost all qualitative parameters including the morphology, the root development, and photosynthesis, while also maintaining high fruit quality.